A novel PV/T-air dual source heat pump water heater system: Dynamic simulation and performance characterization. (15th September 2017) - Cai, Jingyong; Ji, Jie; Wang, Yunyun; Zhou, Fan; Yu, Bendong
Highlights: The PV/T evaporator and air source evaporator connect in parallel and operate simultaneously. A dynamic model is developed to simulate the behavior of the system. The thermal and electrical characteristics of the PV/T evaporator are evaluated. The contribution of the air source evaporator and PV/T evaporator has been discussed. Abstract: To enable the heat pump water heater maintain efficient operation under diverse circumstances, a novel PV/T-air dual source heat pump water heater (PV/T-AHPWH) has been proposed in this study. In the PV/T-AHPWH system, a PV/T evaporator and an air source evaporator connect in parallel and operate simultaneously to recover energy from both solar energy and environment. A dynamic model is presented to simulate the behavior of the PV/T-AHPWH system. On this basis, the influences of solar irradiation, ambient temperature and packing factor have been discussed, and the contributions of air source evaporator and PV/T evaporator are evaluated. The results reveal that the system can obtain efficient operation with the average COP above 2.0 under the ambient temperature of 10 °C and solar irradiation of 100 W/m 2 . The PV/T evaporator can compensate for the performance degradation of the air source evaporator caused by the increasing condensing temperature. As the evaporating capacity in PV/T evaporator remains at relatively low level under low irradiation, the air source evaporator can play the main role of recovering heat. Comparing the performance of dual source heat pump system employing PV/T collector with that utilizing normal solar thermal collector, the system utilizing PV/T evaporator is more efficient in energy saving and performance improvement.